Tracking children's development over time: The Longitudinal Study of Australian Children Outcome Indices, Waves 2 and 3 - LSAC Research Consortium; Sipthorp, M; the LSAC Research Consortium; Rogers, H; Rothman, S; Berthelsen, D; Wake, M; Misson, S; Sanson, A (My University, 2011)
LSAC's extensive data collection provides a large range of measures on many different aspects of children's functioning, which are needed for answering important questions about child development. The LSAC Outcome Indices are designed to be simple, user-friendly summaries of key child development measures as a tool for communicating otherwise complex research findings for policy-makers, the media, the general public and other data users. The Wave 1 Outcome Indices were published with the initial release of the LSAC data in April 2005. Hence, they have been in the public domain for some time, and have received considerable use and scrutiny. With the release of Waves 2 and 3 data, longitudinal and cross-cohort comparisons of child outcomes are possible. These factors have led to the revision of the Wave 1 Outcome Indices in conjunction with the development of the Wave 2 and 3 Outcome Indices. As such, this paper is intended to describe the construction of the Outcome Indices for Waves 1, 2 and 3 data, as at the time of Wave 3 data release. Except when noted, all analyses presented in this paper use weighted data.
AIFS Research Papers
Keywords: Children -- Outcomes; Childhood and child development; Children; Outcomes; Childhood and child development